Resolving two Haploembia (Embioptera: Oligotomidae) cryptic species: molecular data confirms parthenogenetic females can be distinguished by their antisocial behavior - Kelly, Erin T.; Whittall, Justen B.; Edgerly, Janice S. (Zootaxa, 2018)
The names of two cryptic species of Haploembia found in California are resolved and methods for identification are summarized. Molecular data of the Histone III subunit was used to evaluate color and behavior as species identifiers, confirming that antisocial behavior is a good identifier for the parthenogenetic species (Haploembia tarsalis), whereas the more variable coloration patterns were helpful, but less so. A genome size ratio of 1.44 between the parthenogenetic H. tarsalis and the sexually reproducing H. solieri was observed, along with higher genetic variation within the asexual lineage. This, and the identification of what appears to be a putative hybrid, contributes to current work examining mutation rates and selective pressures on genome size in parthenogenetic populations.